More reading power - Mikulecky, Beatrice S. (Longman, 2004)
More Reading Power, Second Edition, by Beatrice S. Mikulecky and Linda Jeffries, is a student-centered reading skills textbook with a process approach to reading improvement. Its four key sections, designed to be used concurrently, help intermediate to high-intermediate students develop solid reading skills necessary in school, college, or business